From "De arte natandi" to the science of swimming - Pelayo, P. (Biomechanics and Medicine in Swimming IX, 2003)
Between 153 8, date of the first book specifically dedicated to swimming written by Wynman, and 1970, date of the first International symposium on biomechanics and medicine in swimming [organised by J Lewillie and JP Clarys in Brussels], the art of swimming can be described as both the result of the swimmer experience and technical clues discovered by scientists. Hence, swimming has become an important cultural phenomenon where teaching is complex and differs in relation to biomechanical concepts ofthe same period. From 1538 to 1970, numerous written works (more than 500 before 1900) and swimming films have been analysed in relation to technical and teaching concepts. Moreover, the evolution of biomechanical knowledge and regulation constraints were put forward to explain balance, breathing and propulsion changes in the modern swimming strokes. The purpose of this historical review was to analyse the evolution of learning methods and stroke technique in relation to biomechanical concepts.